Effects of yoga training applied with telerehabilitation on core stabilization and physical fitness in junior tennis players: A randomized controlled trial - Gergüz, Çağla; Aras Bayram, Gülay (S. Karger AG, 2023)
Introduction: This study aimed to investigate the effects of yoga training applied with telerehabilitation on core stability, and strength, balance, flexibility, upper extremity stability, body awareness, and quality of life in tennis players aged 6–18 years. Methods: Forty tennis players were randomly divided into two groups to participate in this study. The control group (n = 20) continued tennis training and was informed about the importance of the core region. The yoga group (n = 20) received yoga training with telerehabilitation 2 days a week for 8 weeks. Athletes were evaluated with sport-specific core muscle strength and stability tests, the back scratch test, the sit and reach test, the flamingo balance test, the y-balance test (lower quarter), the upper extremity closed kinetic chain stability test, the SF-36, and body awareness questionnaires. Measurements have been done in the tennis club before and after the 8 weeks of training. Results: A significant increase was determined in core strength and stability, sit and reach, back scratch test, upper extremity stability, and body awareness questionnaire in the yoga group (p < 0.001). Flamingo and Y balance test results were significant (p < 0.002). Positive improvements were found in SF-36s energy-fatigue level, mental well-being, social function (p < 0.042), pain (p < 0.005), and general health (p < 0.001). A significant increase was observed in the core strength measurement mean score in the control group (p < 0.018). Sit and reach test, flamingo test, and body awareness questionnaire were found to be significant after the intervention (p < 0.001). Significant improvements were found in the pain (p < 0.042), and mental well-being (p < 0.001) sub-parameters of the SF-36. Conclusion: In the study, it was concluded that yoga training applied with telerehabilitation in tennis players aged 6–18 has a positive effect on core strength, and stabilization, physical fitness parameters, quality of life, and body awareness.
Auswirkungen von Yogatraining in Verbindung mit Telerehabilitation auf die Rumpfstabilisierung und die körperliche Fitness bei jungen Tennisspielern: Eine randomisierte kontrollierte Studie
Keywords: Telerehabilitation; Tennis; Yoga